Rethinking a curriculum that includes the Venezuelan student's language in schools in Boa Vista-RR. (Interdisciplinary Studies Journal, 2024)
The state of Roraima receives a large number of immigrants from Venezuela. Upon entering school, they are faced with a language different from their own, which becomes a challenge. Considering this scenario, the present study aimed to analyze how the curriculum should be structured to include the Venezuelan student's language in schools in Boa Vista-RR. To achieve this goal, the study adopted a qualitative approach with a descriptive focus, using bibliographic research. Numerous authors contributed to the foundation of this study, with notable mentions of Sousa (2022), who addresses the immigrant student in Roraima; Gomes (2007), who defines the curriculum; and Vieira and Liberari (2021), who discuss a curriculum designed to meet the needs of the Venezuelan student, considering their cultural and linguistic context. As a result, the importance of structuring a curriculum that includes not only the official language of Brazil but also the Venezuelan student's mother tongue was highlighted.
Keywords: School Curriculum; Language; Venezuelan Student